2021
DOI: 10.1186/s13052-021-01115-3
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding lowers the odds of childhood diarrhea and other medical conditions: evidence from the 2016 Ethiopian demographic and health survey

Abstract: Background Lack of exclusive breastfeeding during the first 6 months of infant life contributes to childhood morbidity and mortality. This study aimed to investigate the association of exclusive breastfeeding and childhood illnesses in Ethiopia. Methods A secondary data analysis was conducted using data from the 2016 Ethiopian Demographic and Health Survey (EDHS). Descriptive and multivariable logistic regression analyses were carried out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Out of the 28 studies that included diarrhea as the outcome variable, nearly all studies ( n = 27; one meta-analysis, 19 cross-sectional, five cohort, and two case–control studies) found a statistically significant decrease in the risk of diarrhea in children who were EBF [ 14 , 18 , 24 , 27 , 31 , 39 , 42 , 43 , 53 , 55 , 56 , 58 , 60 , 62 , 63 , 65 , 66 , 67 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 ]. Only one paper did not find a statistically significant association, and this analysis looked at diarrhea and ARI comorbidity [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 28 studies that included diarrhea as the outcome variable, nearly all studies ( n = 27; one meta-analysis, 19 cross-sectional, five cohort, and two case–control studies) found a statistically significant decrease in the risk of diarrhea in children who were EBF [ 14 , 18 , 24 , 27 , 31 , 39 , 42 , 43 , 53 , 55 , 56 , 58 , 60 , 62 , 63 , 65 , 66 , 67 , 69 , 70 , 71 , 72 , 74 , 75 , 76 , 77 , 78 ]. Only one paper did not find a statistically significant association, and this analysis looked at diarrhea and ARI comorbidity [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…All papers that analyzed fever as the outcome factor reported a decrease in the risk of fever in children who were EBF ( n = 5; 4 cross-sectional, 1 cohort) [ 21 , 66 , 67 , 69 , 74 ]. All articles that examined urinary tract infection ( n = 1), sepsis ( n = 1), acute otitis media ( n = 3), HFMD infection ( n = 1), and broad category of infections ( n = 2) reported a reduced risk of these conditions in children who were EBF [ 12 , 14 , 30 , 33 , 36 , 45 , 64 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1 , we summarized studies on breastfeeding and infections published since 1st January 2010 [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. WHO recommended that all mothers should be supported to initiate breastfeeding as soon as possible after birth, within the first hour after delivery [ 59 ].…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%
“…A recent nationally representative survey in Ethiopia (1034 infants aged < 6 months) demonstrated that exclusively breastfed subjects had a significant reduction in the frequency of illness with fever in the last 2 weeks compared to non-exclusively breastfed infants. Particularly, exclusively breastfed babies had lower odds ratio (OR) of having an illness with cough (OR 0.38) and diarrhea (OR 0.33) [ 57 ]. This finding agreed with the results of a large USA prospective longitudinal study (6861 children with a follow-up of 4 years) that found an inverse significant association between breastfeeding and the risk of respiratory infections with fever (OR 0.82), otitis media (OR 0.76), and infectious gastroenteritis (OR 0.55) at 3–6 months of life.…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%
See 1 more Smart Citation